Evidence-based healthcare competence of social- and healthcare educators : A cross-sectional study - Immonen, Kati (Wiley-Blackwell, 2025)
Aim: The purpose of the study was to describe social and healthcare educators' evidence-based healthcare competence and explore the associated factors.
Design: A descriptive, cross-sectional study was carried out.
Methods: The research spanned 5 universities, 19 universities of applied sciences, and 10 vocational colleges in Finland from September to December 2022. Social and healthcare educators (n = 256), of which 21 worked at universities, 176 worked at universities of applied sciences, and 49 worked at vocational colleges. Data collection employed a self-assessed instrument that was designed to measure evidence-based healthcare competence based on the JBI Model of Evidence-based Healthcare. Competence profiles were formed using K-cluster grouping analysis.
Results: The educators' self-evaluations of their level of evidence-based healthcare competence were generally at a satisfactory level, with subsequent analyses identifying four distinct profiles of evidence-based healthcare competence. The profiles demonstrated statistically significant differences in terms of evidence synthesis and evidence transfer competencies. The factors associated with evidence-based healthcare competence included level of education, the year in which a professional had obtained their highest degree, current organization of employment, and participation in continuing education.
Conclusions: Educators require various types of support for developing high levels of evidence-based healthcare competence. The identification of distinct competence profiles can be pivotal to providing educators with training that is tailored to their exact needs to provide an individualized learning path. WHAT PROBLEM DID THE STUDY ADDRESS?: Educators value the role of evidence in teaching, which reinforces the need to integrate aspects of the JBI Model of evidence-based healthcare into educators' competencies. Aspects of the JBI Model of evidence-based healthcare have not been holistically measured, with only certain components of the model considered separately. Educators need to better understand the global healthcare environment so they can identify research gaps and subsequently develop healthcare systems through their educational role. Higher academic education, work experience, organizational support, and continuous education play essential roles in the development of educators' evidence-based healthcare competence. WHAT WERE THE MAIN FINDINGS?: Educators generally have high levels of competence in evidence-based healthcare. Educators have mastered the different components of the JBI model of evidence-based healthcare but need to improve in areas such as the transfer and implementation of evidence. WHERE AND ON WHOM WILL THE RESEARCH HAVE AN IMPACT?: Determining evidence-based healthcare competence profiles for educators can be used to provide individualized learning paths for the development of evidence-based healthcare competence. Educators need to further develop their competence in evidence-based healthcare to ensure successful implementation and high-quality education in the future.
Patient or public contribution: No patient or public contribution.